The effect of a pelvic compression belt on postural stability in postpartum women - Vatter, R. F.; Segura-Velandia, D.; Moore, I. S.; Mears, A. C. (Sports Engineering, 2025)
The health benefits of physical activity are well known, however, for the postpartum population there are barriers to retuning to physical activity such as pelvic pain and a fear of movement. Pelvic pain can manifest from instability in the pelvic region and lead to impaired balance and postural stability, exacerbating fear of movement. This study aimed to assess the effect of pelvic compression on postural stability in postpartum women and a nulligravida control cohort. The participants` postural stability was measured using an inertial measurement unit, and the outcome measures JERK, mean velocity, trajectory area index, and root mean squared acceleration calculated, across two visual conditions (eyes open and eyes closed) during tandem and unilateral stances with and without the use of a pelvic compression belt. Significant improvements were observed, particularly in root mean square acceleration (p = 0.003) and JERK (p = 0.001), when a compression belt was used indicating enhanced postural stability, with the participants moving more smoothly and less intensely when maintaining balance. The effect of compression was highly individualised, suggesting pelvic compression could serve as an effective intervention to improve postural stability, though individual responses warrant a tailored approach for optimal results.